2018
DOI: 10.1519/jsc.0000000000002339
|View full text |Cite
|
Sign up to set email alerts
|

Time Response of Photobiomodulation Therapy on Muscular Fatigue in Humans

Abstract: The aim of this study was to identify the effects of two different time responses on fatigue of knee extensor. Sixteen male volunteers (26±6.0 years 81±12 kg, and 181±7.4 cm) participated of study. Participants performed the same protocol in five sessions, [control, placebo (placebo applied both 6 hours before and immediately before the test), 6h before + immediately before (PBMT applied both 6 hours before and immediately before the test), 6h before (PBMT applied 6 hours before and placebo applied immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
0
24
2
3
Order By: Relevance
“…Authors did not observe effects at 5 mins time-response window, but found increased muscular ATP and increased performance in mice when 3 h, 6 h and 24 h (1-day) time-response windows were used, with better results in favor of 6 h time-response window. Interestingly, the clinical outcomes observed both by Rossato et al [ 35 ] and by our findings did not corroborate with the outcomes observed by Ferraresi et al both in cultured myotubes (in vitro) [ 43 ] and mice (in vivo) [ 38 ]. Despite Ferraresi et al [ 38 ] state that “ Although the time response in mice and humans is not the same, athletes might consider applying LEDT at 6 h before competition .”, the outcomes from both randomized controlled trials performed with human volunteers showed that indeed the time-response window in mice and humans is not exactly the same.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Authors did not observe effects at 5 mins time-response window, but found increased muscular ATP and increased performance in mice when 3 h, 6 h and 24 h (1-day) time-response windows were used, with better results in favor of 6 h time-response window. Interestingly, the clinical outcomes observed both by Rossato et al [ 35 ] and by our findings did not corroborate with the outcomes observed by Ferraresi et al both in cultured myotubes (in vitro) [ 43 ] and mice (in vivo) [ 38 ]. Despite Ferraresi et al [ 38 ] state that “ Although the time response in mice and humans is not the same, athletes might consider applying LEDT at 6 h before competition .”, the outcomes from both randomized controlled trials performed with human volunteers showed that indeed the time-response window in mice and humans is not exactly the same.…”
Section: Discussioncontrasting
confidence: 99%
“…Our outcomes agreed that PBMT-sMF is able to increase performance, however, with a single irradiation applied at 5 mins, 3 h or 6 h before a high intensity exercise protocol with decreased effects when PBMT-sMF is applied 1-day (24 h) before the exercise activity. We believe that the extensive optimization of parameters previously performed with the same PBMT-sMF technology used in our study [ 10 , 15 , 19 21 ], and the increased effects of the synergistic use of three wavelengths [ 3 ], besides the combination of PBMT with sMF [ 28 ], which allowed for only one treatment within 6 h to have positive effects instead two treatments (6 h and 5 mins before) as previously observed [ 35 ]. Thus, we believe that our study brings new knowledge to the existing evidence body in literature.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations